Characteristics and Addiction of Gadget in Adolescent During the Covid-19 Pandemic - Gani Apriningtyas Budiyati; Nilam Purwaningrum; Yuliatil ‘Adawiyah; I Made Moh. Yanuar Saifudin (Global Health Science Group, 2021)
Gadgets are growing rapidly. Gadgets can be used as a medium to find information, entertainment, and interaction. This pandemic condition causes teenagers to often engage in activities in front of gadgets. Conditions in the long term can cause dependence and adverse health effects. The aim of this study is to know the characteristics of adolescents and the use of gadgets in adolescents during the covid-19 pandemic. This research is descriptive research. The population of this study is were adolescents aged 12-18 years. The number of sample in this study is 135 respondents. The analysis used is univariable analysis. The sampling technique used in this study is accidental sampling. Results of this study showing that the majority of adolescents aged 16 years (85.9%), the majority of education is high school (95.6%), the majority of the purpose of using gadgets is for social media (46%), the tasks that teenagers get during the pandemic are the majority 5 tasks (83%) . Most gadgets used during online learning are <3 gadgets (88.1%). For gadgets that are often used, the majority of respondents use mobile phones (97%) and the majority of respondents are in the category of gadget addiction (67%). The characteristics of adolescents in this study are mostly 16 years old, have high school education, with the aim of using gadgets to socialize media. The tasks they have to do in a day during the pandemic 5 tasks, with the number of gadgets used <3 gadgets. Teenagers use mobile phones more often than other gadgets and most of these respondents are addicted to using gadgets.